Pengaruh Kepribadian Hardiness dengan Optimisme Masa Depan pada Siswa MAN 2 Wonosobo - Akhmad Zahid; Eni Rindi Antika (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to determine the effect of hardiness personality on future optimism in MAN 2 Wonosobo students. This research uses quantitative research with ex post facto design. The population in this study were students of class XII at MAN 2 Wonosobo, amounting to 421 students. The sample of this study amounted to 201 students who were taken using simple random sampling technique. Data were collected using the personality hardiness scale and future optimism scale. Hardiness personality scale consists of 33 items with a range of validity coefficient values ​​of 0.407 to 0.763 and reliability of 0.947 so that it can be said to be valid and reliable. Furthermore, there are 21 future optimism scales which have a validity coefficient range of 0.303 to 0.824 and a reliability of 0.913 so that it can be said to be valid and reliable. This study uses two data analysis techniques, namely descriptive analysis and simple linear regression analysis. Hardiness personality is in the moderate category (M=102,37; SD=7.33). Future optimism is in the high category (M=75.51; SD=9.05). The results of a simple linear regression test can be obtained, namely = -0.054, R2 0.002, p> 0.05 which indicates that hardiness personality has no significant effect on future optimism in MAN 2 Wonosobo students. Hardiness personality only contributes 2% to the future optimism of MAN 2 Wonosobo students. For further researchers, it is recommended to conduct research using different methods that can aim to reveal the causality relationship of hardiness personality to future optimism. As a development, research can use other variables that can affect future optimism in students or can reveal differences in the relationship between hardiness personality and future optimism when viewed from gender, class, and so on.